2018
DOI: 10.32479/ijeep.7111
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Global warming is one of the most significant challenges facing the world today, as it poses an alarming threat to the entire ecosystem, human health, the economy, and national security. With the ever-increasing emission of carbon dioxide and other greenhouse gases, there has been a progressive rise in mean temperatures recorded, causing global sea levels to increase as a result of the acceleration of warming oceans, shrinking ice sheets and glacial retreat. Global warming has heightened the ferocity and frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The summary details of all variables involved in this study are shown in Table 1. The underlying framework of the model specification is based on the studies of Lean & Smyth (2019), Sebri & Ben-Salha (2014), Farhani et al (2014), and Rasiah, Guptan, & Habibullah (2018). The generalizedmethod-of-moments (GMM) technique (Holtz-Eakin, Newey, & Rosen 1988; Arellano & Bond, 1991;Arellano & Bover, 1995;Blundell & Bond, 1998) was utilized to analyse the dynamic carbon emission model by using annual data of 125 countries for the 2000 to 2014 period, as this was the only time period where there was complete data for the dependent and independent variables across all 125 countries.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The summary details of all variables involved in this study are shown in Table 1. The underlying framework of the model specification is based on the studies of Lean & Smyth (2019), Sebri & Ben-Salha (2014), Farhani et al (2014), and Rasiah, Guptan, & Habibullah (2018). The generalizedmethod-of-moments (GMM) technique (Holtz-Eakin, Newey, & Rosen 1988; Arellano & Bond, 1991;Arellano & Bover, 1995;Blundell & Bond, 1998) was utilized to analyse the dynamic carbon emission model by using annual data of 125 countries for the 2000 to 2014 period, as this was the only time period where there was complete data for the dependent and independent variables across all 125 countries.…”
Section: Methodsmentioning
confidence: 99%
“…All economic data used in this study were sourced from the World Development Indicators published by the World Bank. The model used in this study was based on Lean & Smyth (2010), Sebri & Ben-Salha (2014), Farhani, Chaibi, & Rault, 2014), and Rasiah, Guptan, & Habibullah (2018), the empirical long-run relation between carbon emissions, real GDPC, energy use, TO, and FD is written in the following form: and with the GMM procedure, it is estimated the following carbon emissions model equation:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of the fossil fuel consumption, the generation of energy from fossil fuels is expected to emit more carbon dioxide and is thus considered destructive for the atmosphere (Rasiah et al, 2018, Sarkodie & Strezov, 2018. Energy generation from renewable sources, on the other hand, is more sustainable for the environment in the sense that such processes emit lesser to no carbon dioxide emission (Zoundi, 2017;Shahbaz & Sinha, 2019).…”
Section: B Results Of the Pedroni Panel Cointegration Testmentioning
confidence: 99%